Aplikasi Crowdsource pada Sistem Pencarian Tutor Berbasis Web dan Android - Ibe, Sontama Baktiano; Handojo, Andreas; Wibowo, Adi (Jurnal Infra, 2015)
Nowadays, students are having difficulties looking for tutoringservices. The obstacles are, for example, difficulty to find thetutor, fee that does not fit to the budget, and inflexible schedule.Furthermore, tutors are having difficulties looking for studentswho need his or her service.Due to these reasons, this thesis is intended to create a systemwith web and Android apps that can facilitate tutors and studentsin meeting and holding learning activities. This application can beused by a student looking for an appropriate tutor and also by atutor listing matching students. This application can display themeeting location with the help of Google Map. Based on thequestionnaire result, it can be concluded that most of the usersare satisfied with the application.